Pengaruh Kualitas Produk, Promosi dan Kualitas Layanan terhadap Keputusan Pembelian Produk Sinar Serayu Abadi Semarang - Yuliati, Yuliati; Indah, Nur (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This research is motivated by the decline in sales turnover of Sinar Serayu Abadi Semarang from 2020 to 2021 and then 2021 to 2022 and the existence of research gaps from previous research. This aim is to recognize and analyze the influence of Product Quality, Promotion and Service Quality simultaneously on Product Purchasing Decisions by Sinar Serayu Abadi Semarang customers.The population is all consumers of Sinar Serayu Abadi. Because the number is infinite, this sampling technique uses the Lemeshow formula (97). Data collection in this research used a questionnaire or questionnaire. Then processed using SPSS version 25. The results of this research indicate that there is one variable that does not influence purchasing decisions, namely product quality. So H1 is rejected, while H2 and H3 are accepted. It is proven from the results of the t test that has been carried out which results: Presentation of Product Quality Variables has a t-value of 0.790 < t table 1.986 with a significant value of 0.431 > α 0.05. Promotion Variable Presentation has a t-count value of 3.421 > t-table 1.986 with a significant value of 0.001 less than α 0.05. Service Quality has a t-value of 4.971 > ttable 1.986 with a significant value of 0.000 which is lower than α 0.05. This can be explained that not all product qualities influence the purchasing decision process. However, in general, product quality is what determines whether the product will last a long time or not on the market.Based on the F-test, the result of F-count are 53.477>F-table 2.70 with a significant value of 0.000 which is lower than α 0.05. These result explain that Product Quality, Promotion, Service Quality simultaneously have a significant influence on purchasing decision. Keywords: Product Quality, Promotion, Service Quality and Purchasing Decision.